THE INFLUENCE OF DISCIPLINE AND ABILITY ON EMPLOYEE PERFORMANCE - Muhamad Guruh; Fitri Sabina; Surya Budiman (International Journal Management and Economic, 2024)
This research aims to determine the effect of discipline and ability on employee performance in the assembly section of PT. Hilex Indonesia both partially and simultaneously. The method used is a quantitative method. The sampling technique used was random sampling with a sample of 180 respondents. Data analysis used multiple linear regression analysis with SPSS 26.00. The results of this research are that discipline has a significant effect on employee performance, and workability has a significant effect on employee performance. Discipline and workability simultaneously have a significant effect on employee performance.